Uma abordagem multicritério para a seleção de indicadores de desempenho em um centro de serviços compartilhados - Guimarães, Tiago Lima [UNESP]; Tramarico, Claudemir Leif (Associacao Brasileira de Engenharia de Producao - ABEPRO, 2025)
This paper examines the prioritization of performance indicators in Shared Service Centers (SSC) using the Analytic Hierarchy Process (AHP) method. The primary objective is to identify and prioritize the most relevant indicators for evaluating SSC performance, providing a robust basis for managerial decision-making. The relevance of the research is highlighted by the growing importance of SSC in the operational optimization of organizations and the need for effective performance measurement tools. The approach adopted is multi-criteria, allowing for the selection and prioritization of financial and non-financial indicators, according to the specific needs of SSCs. The findings reveal that adaptability and innovation are the most critical dimensions for the success of SSCs. The results obtained provide a detailed understanding of the most significant areas for SSC performance management, establishing a solid basis for strategic decision-making. The paper enriches the existing literature by demonstrating the practical application of analytical method in performance management, offering a useful approach for prioritizing indicators and suggesting directions for future research.